2017
DOI: 10.1002/bdd.2058
|View full text |Cite
|
Sign up to set email alerts
|

The absorption kinetics of ketoconazole plays a major role in explaining the reported variability in the level of interaction with midazolam: Interplay between formulation and inhibition of gut wall and liver metabolism

Abstract: The impact of different single oral doses of ketoconazole (KTZ) (100, 200 and 400 mg) and of staggering its dosage (400 mg at -12, -2, 0, 2 and 4 h), with respect to the administration of a single 5 mg oral dose of midazolam (MDZ) on the extent of inhibition of the metabolism of the latter, was evaluated in healthy subjects in two separate studies. Escalation of the ketoconazole dosage resulted in 2.3 (1.9), 2.7 (1.7) and 4.2 (2.5) -fold increases in the mean AUC (and C ) values of midazolam. Dose-staggering w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…a variable content of CYP1A1 in hepatocytes including the rather unlikely lower limit of f m,CYP1A1 = 0.0. Focusing on the inhibitory potency on CYP3A4 in hepatocytes using midazolam as a sensitive CYP3A4 substrate, results of this study revealed that the significant decrease in clearance of midazolam with fixed-dose antiretroviral combinations containing strong CYP3A4 inhibitors cobicistat, ritonavir, atazanavir, and darunavir, as well as clarithromycin, and ketoconazole is consistent with previous clinical studies (Table S7) [16,[58][59][60][61]. Based on the published clinical literature [16], no DDIs were expected with CYP3A substrates for abacavir/dolutegravir/lamivudine (components of TRIUMEQ ® ) or emtricitabine/rilpivirine/tenofovir disoproxil (components of COMPLERA ® ), which is consistent with the in vitro data observed with recombinant CYP3A4 and in human hepatocytes using midazolam as a substrate in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…a variable content of CYP1A1 in hepatocytes including the rather unlikely lower limit of f m,CYP1A1 = 0.0. Focusing on the inhibitory potency on CYP3A4 in hepatocytes using midazolam as a sensitive CYP3A4 substrate, results of this study revealed that the significant decrease in clearance of midazolam with fixed-dose antiretroviral combinations containing strong CYP3A4 inhibitors cobicistat, ritonavir, atazanavir, and darunavir, as well as clarithromycin, and ketoconazole is consistent with previous clinical studies (Table S7) [16,[58][59][60][61]. Based on the published clinical literature [16], no DDIs were expected with CYP3A substrates for abacavir/dolutegravir/lamivudine (components of TRIUMEQ ® ) or emtricitabine/rilpivirine/tenofovir disoproxil (components of COMPLERA ® ), which is consistent with the in vitro data observed with recombinant CYP3A4 and in human hepatocytes using midazolam as a substrate in the present study.…”
Section: Discussionsupporting
confidence: 88%
“…The default PBPK models for carbamazepine, ketoconazole, and rifampicin in Simcyp Simulator were used (Almond et al, 2016;Liu et al, 2017). The predictive performance of the PBPK models in paediatric population need to be verified prior to their further use, since the original models were developed in adults.…”
Section: Pbpk Model Prediction Of Drug Interactions With a Range Of Cmentioning
confidence: 99%
“…The induction of CYP3A and CYP2C8 was modeled by an increase in protein synthesis (turnover) rate constant in hepatocytes and enterocytes according to an enzyme turnover model (Almond et al, 2016). Ketoconazole inhibits CYP3A4 and CYP2C8 competitively with an inhibitory constant (Ki u ) of 15 nmol/L (Liu et al, 2017) and 2.2 μmol/L, respectively. PBPK simulations were carried out with n = 50 (40% of female) for each age band.…”
Section: Implementation Of Pbpk Modeling Approach To Evaluate Drug Inmentioning
confidence: 99%
“…Interests on intestinal versus liver metabolism have been increasing. The intestine is seriously being considered in physiologically‐based pharmacokinetic (PBPK) modeling (Badhan, Penny, Galetin, & Houston, ; Cong, Doherty, & Pang, ; Dressman, Thelen, & Jantratid, ; Fenneteau, Poulin, & Nekka, ; Guo et al, ; Liu et al, ; Mano, Sugiyama, & Ito, ; Pang, ; Parrott & Lavé, ; Zhang et al, ), especially for drug metabolism, drug transport and drug–drug interactions (Chen et al, ; Duan, Zhao, & Zhang, ; Marzolini et al, ; Yoshikado et al, ). In some rarely documented instances, intestinally formed metabolites have been found to be inhibitors of liver metabolism (Quinney et al, ), causing changes in protein (enzyme or transporter) contents in mechanism‐based inhibition, MBI (Guo et al, ; Moj et al, ; Quinney et al, ; Rowland Yeo et al, ; Zhang et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Since the intestine is divided into three segmental regions (duodenum, jejunum, and ileum), catenary models that incorporate sequential processing of drugs within the segments have evolved for consideration of the different sites of absorption and metabolism (Agoram, Woltosz, & Bolger, 2001;Bolger, Lukacova, & Woltosz, 2009;Tam, Tirona, & Pang, 2003;Yu & Amidon, 1999;Yu, Lipka, Crison, & Amidon, 1996). The popularized advanced dissolution absorption metabolism (ADAM) Liu et al, 2017;Rowland Yeo, Jamei, Yang, Tucker, & Rostami-Hodjegan, 2010) and advanced compartmental absorption and transition (ACAT) (Bolger et al, 2009;Daga, Bolger, Haworth, Clark, & Martin, 2018;Hens & Bolger, 2019) models are based on these principles, emphasizing the use of the drug physicochemical properties and drug permeability on drug absorption and disposition. Interests on intestinal versus liver metabolism have been increasing.…”
mentioning
confidence: 99%